A low-cost paper-based platform for fast and reliable screening of cellular interactions with materials - E. Rosqvist; E Niemelä; J. Frisk; H. Öblom; R. Koppolu; H. Abdelkader; D. Soto Véliz; M. Mennillo; A.P. Venu; P. Ihalainen; M. Aubert; N. Sandler; et al. (ROYAL SOC CHEMISTRY, 2022)
A paper-based platform was developed and tested for studies on basic cell culture, material biocompatibility, and activity of pharmaceuticals in order to provide a reliable, robust and low-cost cell study platform. It is based upon a paper or paperboard support, with a nanostructured Latex coating to provide an enhanced cell growth and sufficient barrier properties. Wetting is Limited to regions of interest using a flexographically printed hydrophobic polydimethylsiloxane Layer with circular non-print areas. The nanostructured coating can be substituted for another coating of interest, or the regions of interest functionalized with a material to be studied. The platform is fully up-scalable, being produced with roll-to-roll rod coating, flexographic and inkjet printing methods. Results show that the platform efficiency is comparable to multi-well plates in colorimetric assays in three separate studies: a cell culture study, a biocompatibility study, and a drug screening study. The color intensity is quantified by using a common office scanner or an imaging device and the data is analyzed by a custom computer software without the need for expensive screening or analysis equipment.